PROFIL IMAM MALIK SEBAGAI MUHADDITS DAN FAQIH DALAM SEJARAH PENDIDIKAN ISLAM DAN ILMU PENGETAHUAN ISLAM - amir, dinasril amir (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2019)
Imam Malik is a knowlegeable and very famous character. In the past he was viewed an educated and religious person, and also a priest of the people in education. So that he is best known as Imam Dar Athjrat ( Imam of Madina). Imam Malik is the founder and builder of maliki madhhab, whose thought and madhhab depend on the sunnah of the prophet and his companions. Many of his opuses are recognized and well-known, one of them is the book of hadith and fiqh al-muwattha (well-trodden path).